Obstetrical Characteristics and Glucose Profile of Singleton Primigravid Women with Gestational Diabetes Mellitus in Meru Mother and Child Health Clinic, Malaysia - Ahmad Shuhaimi, Farhanah; Abdul Hamid, Syahrul Bariah (Jurnal Gizi dan Pangan, 2024)
This study aims to explore the baseline obstetric characteristics of singleton, primigravid women with Gestational Diabetes Mellitus (GDM) from an experimental study. A total of 58 subjects with GDM, who were solely on diet control, were recruited from Meru Health Clinic in Selangor. The majority of the subjects (97%) were Malay. The mean age of the subjects was 27.59±3.2 years, with a pre-pregnancy weight of 68.86±17.8 kg, a height of 1.56±0.1 m, and Body Mass Index (BMI) of 28.08±6.7 kg/m2. Most subjects in this study (93%) were diagnosed with GDM at their first Oral Glucose Tolerance Test (OGTT), conducted at a mean gestational age of 18.93±2.8 weeks. The OGTT readings at diagnosis were 5.1±0.6 mmol/L for Fasting Blood Glucose (FBG) and 7.9±1.5 mmol/L for 2-Hour Postprandial (2HPP). The Blood Sugar Profile (BSP) levels were recorded as follows: fasting at 4.8±0.4 mmol/L, pre-lunch at 5.1±0.5 mmol/L, post-lunch at 5.3±0.5 mmol/L, and post-dinner at 5.3±1.5 mmol/L. Macronutrient intake was within the recommended guidelines. The subjects delivered at a mean gestational age of 38.8±1.1 weeks, with a mean birth weight of 2.99±0.4 kg. No incidences of macrosomia were recorded in this study. In conclusion, the subjects underwent early GDM screening, had well-controlled antenatal blood glucose levels, and experienced no adverse pregnancy outcomes.